Disaster Communication in Community Social Systems: (Study on Mount Semeru Eruption Case) - Anindya Septiana Arfiani; Sayyaf Nasrul Islami (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2023)
The Eruption of Mount Semeru that occurred in Lumajang Regency in 2021 has claimed 51 lives and dozens are missing. Disaster Communication is present in an effort to minimize victims and affected areas. The purpose of this study is to determine the form of disaster communication carried out in a state social system during a volcanic eruption disaster. This research uses a descriptive qualitative research method with a case study approach that specifically discusses the case of the eruption of Mount Semeru. The author describes disaster communication carried out by the government and related parties in order to respond to the disaster and then minimize its impact. The author also finds the role of online media both social media and news media in maximizing this disaster communication. The government as the center of the social system uses direct communication. The choice of language and diction that is firm and focused is intended so that those engaged in the field do not hesitate in making decisions in accordance with pre-disaster procedures that have been directed beforehand.